Model Psikoterapi Zikir dalam Meningkatkan Kesehatan Mental - Daimul Ikhsan; Muhammad Irsyadi Fahmi; Asep Mafan (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This article is structured to examine the Islamic psychotherapy model using zikr with saying